Do swimmers conform to criterion speed during pace-controlled swimming in a 25-m pool using a visual light pacer? - Gonjo, T.; McCabe, C.; Coleman, S.; Soares, S.; Fernandes, R. J.; Vilas-Boas, J. P.; Sanders, R. (Sports Biomechanics, 2021)
The purpose of this study was to investigate whether swimmers follow the instructed speed (vtarget) accurately with the aid of a commercial visual light pacer during front crawl and backstroke swimming in a 25 m pool. Ten male swimmers performed 50 m front crawl and backstroke at different speeds (controlled by a visual light pacer) in a 25 m pool. The mean speed during the 50 m swimming (vS) was quantified from the time measured by a stopwatch. The mean speed of the centre of mass during a stroke cycle in the middle of the pool (vCOM) was calculated from three-dimensional coordinates obtained from Direct Linear Transformation of two-dimensional digitised coordinates of 19 segment endpoints for each of six cameras. Swimmers achieved accurate vS in front crawl and backstroke (ICC = 0.972 and 0.978, respectively). However, vCOM for the single mid-pool sample had lower correlations with vtarget (ICC = 0.781 and 0.681, respectively). In backstroke, vCOM was slower by 4.1-5.1% than vtarget. However, this was not the case in front crawl (1.0-2.7%). With the use of a visual light pacer, swimmers can achieve accurate mean speed overall but are less able to achieve the target speed stroke by stroke.